IMPLEMENTASI MODEL THINK PAIR SHARE (TPS) BERBANTU MEDIA RULES CARD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA KEBERAGAMAN INDONESIAKU SISWA KELAS 5 SD SDN RANCAPURUT - Rahma Nur Afifah; Fachrul Isha Mahendra; Lilis Siti Nursyaidah; Pingkan Nelsi Prisma Angelica; Sindi Agustini; Rana Gustian Nugraha (STKIP Subang, 2026)
Low student learning outcomes may be influenced by the use of learning models and media that lack variety, as well as a lack of student engagement during the learning process. Therefore, learning models and media that can enhance student engagement are required. This study aims to examine the implementation of the Think Pair Share learning model assisted by Rules Card media in improving learning outcomes on the theme of Keberagaman Indonesiaku among Year 5 pupils at SDN Rancapurut. This study employed a classroom action research method conducted over two cycles with a sample size of 17 pupils. Each cycle comprised the stages of planning, implementation of actions, observation, and reflection. Data collection was carried out through student learning outcome tests administered in the pre-cycle, at the end of cycle I, and at the end of cycle II, which were then analysed using quantitative descriptive techniques. The results show that the students’ average score increases from 6.76 in the pre-cycle stage to 7.18 in Cycle I and reaches 9 in Cycle II. The percentage of students achieving the learning outcomes also increases from 58.82% in the pre-cycle and Cycle I to 100% in Cycle II. This improvement in learning outcomes indicates that the use of the Think Pair Share model assisted by Rules Card can foster more active and focused learning. Thus, the implementation of the Think Pair Share learning model assisted by Rules Card is effective in improving learning outcomes.